PENGARUH MOTIVASI INVESTASI, KEMAJUAN TEKNOLOGI, STATUS MAHASIWA DAN GENDER TERHADAP MINAT INVESTASI MAHASISWA UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG DI PASAR MODAL SYARIAH - Samba, Alif; Saputri, Yuliana; Listiana, Wulan Dewi; Purwadiansyah, Nur Fuad (Kopertais Wilayah VII Palembang, 2024)
The purpose of this research is to examine the relationship between investment interest among students at Raden Fatah State Islamic University Palembang's Faculty of Islamic Economics and Business and factors such as investment motive, technical advancement, gender, and student status. A total of fifty students who had taken both the portfolio theory and investment analysis classes were polled using a questionnaire. To guarantee data representativeness, the study sample was chosen using the Krejcie-Morgan formula. After running the numbers through SPSS, we found that the variables we looked at significantly affected students' interest in investing; the coefficient of determination (R square) hit 80.6%. Nevertheless, investment interest varied by 19.4 percent due to variables that were not included in this research. These results provide a significant contribution to the creation of student investment education programs that are both more specific and more successful.